Pengaruh Konsumsi Pornografi Terhadap Perkembangan Kognitif, Sosial dan Emosional Remaja - Maftukhah, Weni; Khadijah, Khadijah (MOMENTUM : Jurnal Sosial dan Keagamaan, 2025)
Pornography has become a big problem for teenagers, especially with easy internet access. The aim of this research is to find variables that influence teenagers' tendencies to watch pornographic films and how this impacts their social lives. This research found that several main factors that encourage teenagers to access pornography are peers, environment, social media, sex education lacking, and lack of self-defense. This research uses a qualitative descriptive approach and literature study. By collecting data based on journal articles, literature sources. Apart from that, the negative effects are very large, including disturbances in social, emotional and cognitive aspects. Adolescents who are addicted to pornography tend to experience difficulties socializing, emotional disorders such as difficulty controlling themselves, and decreased cognitive abilities such as difficulty concentrating and thinking critically. Therefore, prevention and treatment must be carried out comprehensively by involving families, schools and the community. To protect teenagers from the bad effects of pornography, comprehensive sex education, parental supervision and moral strengthening from an early age are very important.